FAKTOR SOSIAL DAN EKONOMI YANG MEMPENGARUHI AKSES KESEHATAN ANAK DI KOTA MEDAN: ANALISIS KERENTANAN KESEHATAN ANAK - MAESSTRO BINA UTAMA SIMANJUNTAK (LP2MTBM MAKARIOZ, 2022)
There are approximately 12,105 children who are vulnerable to disease, where the number indicates that around 12,105 children have not received existing health services and access due to economic factors, such as poverty and unemployment who are unable to pay for access and health facilities, in addition to limited access to transportation in reaching access to health for children. In addition, there are other factors, such as social factors, such as understanding of access to health and also people's understanding that doctors are unable to overcome the diseases suffered by their children, as well as understanding that certain diseases result from the curse of God Almighty or due to actions done by parents to others. This study used descriptive analytical method. The population of this study amounted to 12,105 parents whose children did not have access to health in Medan City, where the sample taken amounted to 62 parents whose children did not have access to health in Medan City. Data collection techniques are carried out by observation and documentation studies. The results of the study proved that Medan Kota District is an area in Medan City that gets access to health, where health access is obtained for children in the age range of 0-4 years. Efforts to get access to health are not easy to obtain, where there are the most social factors, namely public stigma about health that hinders the effectiveness of children to get access to health, thus affecting the health vulnerability of children.